Comparison of ultrasound and computed tomography in the diagnosis of malignant ovarian tumours at tertiary care center - Danish, Mozaffar; Bhat, Shreya; Khursheed, Asif; Ahmad, M. Shamim (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Accurate diagnosis of ovarian tumours is a diagnostic challenge. Multiple modes are used for the early detection of ovarian tumours. Early detection provides a survival advantage. Ultrasonography (USG), computed tomography (CT) and magnetic resonance imaging (MRI) are important imaging modalities in this regard. This study aims to compare the diagnostic accuracy of USG and CT imaging in the detection of malignant ovarian tumours. Materials: An observational cross-sectional study is conducted in the department of radiodiagnosis of Narayan medical college and hospital, Bihar over a period of 18 months from August 2021 to March 2024. Fifty-three patients with suspected ovarian malignancy who were not pregnant or had contraindications for administration of contrast media were included in the study. USG, CT and histopathology reports were compared for diagnostic accuracy with respect to different components. Results: Mean age of the patients was seen to be 49.6±13.8 years. Abdominal pain was the most common presentation Majority of the patients had vascular lesions with a well-differentiated margin, heterogenous enhancement and septations. USG and CT agree almost perfectly in, identifying septations, calcification, and in differentiating margin of the tumours and very poorly for the identification of lymphadenopathy. CT had better sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) when compared to USG for diagnosis of ovarian malignancies Conclusions: CT has superior diagnostic accuracy compared to USG for diagnosis of ovarian tumours. However, USG provides similar diagnostic accuracy for identifying septations, calcification, and in differentiating margins of tumours.